World Englishes - Melchers, Gunnel; Shaw, Philip (English language series, 2011)
World Englishes Second Edition provides an overview of the global variation in vocabulary, grammar, phonology and pragmatics of English and includes coverage of spoken varieties that have only recently been researched, as well as changes occurring due to the increasing use of English by non-natives internationally.